Analisis Perilaku Masyarakat Tentang Kepatuhan Hukum Masa Pandemi Covid-19 di Kecamatan Alam Barajo - Yani Simamora, Evita; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2022)
Simamora, Evita Yani. 2021. Analysis of Community Behavior Regarding Legal Compliance with Health Protocols during the Covid-19 Pandemic in Alam Barajo District: Thesis, Pancasila and Citizenship Education Study Program, FKIP Jambi University, Supervisor (I) Drs. Irzal Anderson, M.Sc., (II) Dona Sariani, M.Pd. This study aims to analyze people's behavior regarding legal compliance with health protocols during the covid-19 pandemic in Alam Barajo District, especially residents of the Kenali Besar, Beliung and Bagan Pete villages. This research was conducted using a qualitative procedure with data and data sources obtained from informants, namely the Head of RT 09 Kenali Besar sub-district, residents of Alam Barajo District and several other residents who have different professions, with data collection techniques in the form of interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. Based on the results of data analysis that has been carried out, the findings and conclusions of this study are on the behavior of people who occurred during the covid-19 pandemic in implementing health protocols as a new behavior set by the government to prevent an increase in the spread of covid-19 and reduce transmission of covid-19 In the community, researchers found that many people are aware of and comply with health protocols, but there are still some who are not aware and obedient in carrying out this new behavior such as the 5 M movement, one of which is wearing a mask and keeping a distance/being in a crowd when interacting outside. House. There needs to be proper direction to the community to continue to comply with existing health protocols for the common good.